Risk Associated with Corn Farming in Madura Island - Elys Fauziyah (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2020)
Corn play an essential role in providing food and feed for living things in Madura Island and other parts of the country. More than 80% of the Madura Island farmer, plant this commodity, thereby, making it a productive farming activity in this region. However, its level of productivity is still below average due to the farmers' risk preference. This research, therefore, aims to analyze the risk preferences and inputallocation used in corn farming. The multistage sampling was used to collect data from a total of 120 people in Bangkalan, Sampang, Pamekasan, and Sumenep Regencies located in Madura, while the Kumbhakar parametric model was used to analyze risks. The results showed that farmers are in the Risk Averse category due to poor utilization of seeds, manure, labor, and NPK fertilizer, compared to the recommended level of usage.